Pengaruh Tanaman Kelapa Sawit Terhadap Keseimbangan Air Hutan (Studi Kasus Sub Das Landak, Das Kapuas) - Taufiq, Mohammad; Siswoyo, Hari; WWS, Anggara (Fakultas Teknik, Universitas Brawijaya, 2013)
Development in the area of Landak Sub watershed, Kapuas watershed that quite rapidly also followed by the shrinking of the existing forest area. Reduction in forest area due to land clearing for oil palm tree which absorbs a lot of surrounding water for its growth affect the water balance in the Landak sub-watershed. The aim of this study was to determine the effect of reduction of river flow discharge due to the planting of oil palm tree. The outline of stages of study includes evapotranspiration calculations with the Penman-Monteith, water availability analysis with NRECA Model, water balance analysis with Thornthwaite and Mather model, as well as estimates of river discharge with FJ Mock Model. Based on the results of the study can be seen that the percentage in discharge reduction due to the planting of oil palm tree ranged from 30% to 40%.Keywords: oil palm, water balance